2014
DOI: 10.1128/aac.02097-13
|View full text |Cite
|
Sign up to set email alerts
|

Induction of the Chlamydia muridarum Stress/Persistence Response Increases Azithromycin Treatment Failure in a Murine Model of Infection

Abstract: Viable but noninfectious (stressed/persistent) chlamydiae are more resistant to azithromycin (AZM) in culture than are organisms in the normal developmental cycle. Chlamydia muridarum-infected mice were exposed to amoxicillin to induce the organisms to enter the persistent/stressed state and subsequently treated with AZM. AZM treatment failure was observed in 22% of persistently infected mice, with an average of 321,667 inclusion-forming units (IFU) shed after AZM treatment. Productively infected mice had a 9%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 17 publications
0
48
0
Order By: Relevance
“…By day 9 pci, chlamydial shedding, while still detectable, has declined significantly from peak shedding at day 3 or day 6 pci. By day 27 pci, chlamydial shedding is no longer detectable [ 37 ]. In mice super-infected with HSV-2 on day 9 pci, protection was still observed and the super-infected mice (Cm-9D-H) exhibited significantly higher survival compared to the HSV-2 singly-infected mice (p<0.005), although survival in the Cm-9D-H group dropped slightly to 90% ( Fig 3B ).…”
Section: Resultsmentioning
confidence: 99%
“…By day 9 pci, chlamydial shedding, while still detectable, has declined significantly from peak shedding at day 3 or day 6 pci. By day 27 pci, chlamydial shedding is no longer detectable [ 37 ]. In mice super-infected with HSV-2 on day 9 pci, protection was still observed and the super-infected mice (Cm-9D-H) exhibited significantly higher survival compared to the HSV-2 singly-infected mice (p<0.005), although survival in the Cm-9D-H group dropped slightly to 90% ( Fig 3B ).…”
Section: Resultsmentioning
confidence: 99%
“…If the chlamydial persistent state is, in fact, present in vivo, both detection by culture (persistent chlamydiae are by definition non-cultivable) and treatment of chlamydial infection may be impacted. Persistent chlamydiae are resistant to killing by antibiotics in vitro; and a model of amoxicillin induced C. muridarum persistence in mice indicates persistent chlamydiae are resistant to killing by azithromycin in vivo as well [99]. Furthermore, clinically relevant concentrations of commonly used penicillins induce C. trachomatis persistence in vitro [100].…”
Section: Discussionmentioning
confidence: 99%
“…The meta-analyses of urogenital treatment efficacy found that the efficacy for azithromycin was lower for those with symptomatic infection compared with doxycycline [ 18 ]. It is unclear why this is so and suggests that perhaps a longer duration of azithromycin may be needed [ 34 ] with animal studies suggesting chlamydia shedding was higher in those which were persistently infected and that extended courses can overcome persistent infections [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent in vitro study examining the impact of β-lactam antibiotics on chlamydia persistence [ 39 ] found that all penicillins tested induced the formation of ABs with a 95 % reduction in chlamydia’s infectivity. Upon removal of the antibiotics, the chlamydia became infectious again, but β-lactam-induced persistent chlamydia was less susceptible to azithromycin in vitro [ 35 ]. Therefore, the question begs whether the marked increase in the use of beta-lactam antibiotics in recent years, [ 42 ] including its use in treating increases numbers of syphilis infections among gay men, [ 43 ] is contributing to antibiotic-induced persistence and whether increasing the duration of treatment can overcome this persistence [ 34 ] as has been demonstrated in animals [ 35 ].…”
Section: Introductionmentioning
confidence: 99%